UJI TOKSISITAS SUB KRONIS EKSTRAK DAUN UNGU TERHADAP GAMBARAN HISTOPATOLOGI GINJAL TIKUS PUTIH JANTAN - I Made Dipayana; Niluh Puspita Dewi; Magfira; Joni Tandi; Wayan Wirawan; Meike Rachmawati; Nur Azizah (Postgraduate, University of Mataram, 2024)
Traditional herbal medicine has become increasingly popular as an alternative to conventional medical treatments. Although the plant offers numerous health benefits, caution should be exercised regarding its long-term use. Long-term use of traditional herbal remedies can have detrimental effects on the kidneys. This study was designed to assess the histological changes in the kidneys of male rats following 28 days of purple sage leaf extract administration and to identify potential harmful effects. The study utilized 20 male Wistar rats and utilized a randomized group design for the experimental methodology. Rats were categorized into four distinct groups, consisting of one control group and three treatment groups. The control group received solely sodium chloride, whereas the treatment group 1 (P1) received 500 mg/kg BB of purple sage ethanol extract. Treatment group 2 received up to 2000 mg/kg BB of purple sage ethanol extract, while treatment group 3 received up to 5000 mg/kg BB. The oral examination was conducted for a duration of 28 days. The treatment groups showed an increase in weight and organ index of the right kidney. The findings suggest a potential for toxicity resulting from the administration of purple sage leaf extract over a duration of 28 days.